Love Arabic Movement: Participatory-Based Mentoring for Learning Basic Arabic Writing for Santri at Raudlatut Thalabah Islamic Boarding School Banyuwangi - Nur Maya Badriyatul Jamroh (Simfoni Ilmu Cindekia, 2026)
Mastering basic Arabic writing skills (maharah al-kitabah) for Islamic boarding school students (santri) is often hindered by conventional, passive learning methods. This community service activity aims to improve basic Arabic writing skills and foster learning motivation among santri through the